ANTESEDEN KINERJA: DAMPAKNYA TERHADAP OCB KARYAWAN BRI SYARIAH KANTOR CABANG MALANG - S, Achmad Sani (IQTISHODUNA, 2013)
Little empirical research has looked at casual relationships between transformational leadership,trust and performance impacts on the OCB. Also there is minimal attention to the impact of specific facet oftransformational leadership, trust and performance on OCB of employee BRI Syariah Malang. The purpose ofthis study was to investigate casual relationships through testing path analysis model. This is explanatoryresearch which has goal o test defined hypothesis on the influence of of transformational leadership, trust andperformance toward the OCB of employee. The research population involved 58 employee of BRI SyariahMalang. Quistionnaire is used as research instruments in this research.The result of the research analysisproves transformational leadership, trust and performance give significant influence on the OCB employee.Based on finding, it si further suggested that leader on BRI Syariah Malang should give more attention to thetransformational leadership, trust and performance. The result of this research proves that transformationalleadership, trust and performance give significant influence on OCB.